A student's guide to Maxwell's equations - Fleisch, Daniel A. (Cambridge University Press, 2008)
Gauss's law for electric fields -- Gauss's law for magnetic fields -- Faraday's law -- The ampere-Maxwell law -- From Maxwell's equations to the wave equation